2020
DOI: 10.1590/s1980-6574202000030002
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of plantar pressure and postural control measures of children from 4 to 12 years: analysis by baropodometry

Abstract: Baropodometry is used to map pressure areas and plantar pressure oscillation, however, children's evaluation reliability is not established. To establish the intra-rater and inter-rater reliability of baropodometry for analysis of plantar support and postural control (stabilometry) of children. Materials and Methods: Reliability study. The sample consisted of 112 healthy children of both sexes; aged 4 to 12 years old. For the baropodometer analysis, children were positioned in orthostatic position, bipodal sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this way, our regression analyses showed in children 7–8 years of age that the pressure in the right heel is significantly higher. In this sense, studies such as Bittar et al [ 49 ] and Feka et al [ 48 ] showed that BMI is associated with greater pressure in the hindfoot. Additionally, and regarding the difference in pressure between the left and right leg, we also found that the BMI mainly influences children of the age of 9–10 years, who tend to receive more pressure in the right foot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, our regression analyses showed in children 7–8 years of age that the pressure in the right heel is significantly higher. In this sense, studies such as Bittar et al [ 49 ] and Feka et al [ 48 ] showed that BMI is associated with greater pressure in the hindfoot. Additionally, and regarding the difference in pressure between the left and right leg, we also found that the BMI mainly influences children of the age of 9–10 years, who tend to receive more pressure in the right foot.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, this result is in line and in contrast with previous research, since some studies mention that there is more support in the right foot [ 48 , 50 , 51 ], while Bittar el al. [ 49 ] mention that there is more support in the left foot. Therefore, more studies are still needed to clarify this fact in children because an asymmetrical distribution of loads could lead to asymmetrical growth of the limbs or overloads, leading to postural deformities.…”
Section: Discussionmentioning
confidence: 99%
“…The data collected by baropodometric platforms can be used to analyze the influence of age stages on the static distribution of plantar pressure [4], [8], [12]. Foot pressure distribution (FPD) assessment is clinically important because it may identify anatomic foot deformities and guide the diagnosis and treatment of gait disorders and falls [7], [13].…”
Section: Introductionmentioning
confidence: 99%